The Correlation Between The Duration of Playing Gadgets in Young Children and Parental Anxiety Levels in Sidodadi Village - Patilima, Hamid; Isnawati , Umi (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study aims to analyze the correlation between the duration of gadget play in early childhood and the level of parental anxiety in Sidodadi Village. This study uses an associative method with a quantitative approach. The sampling technique used in this study is the saturated sampling technique found in Non-Probability Sampling. The data collection technique was a questionnaire, the duration of playing gadgets, and the level of parental anxiety. Meanwhile, the analysis technique used is using Pearson Product Moment using SPSS software. The results of the study show that the level of duration of playing gadgets in children in Sidodadi Village, Penarik District, Mukomuko Regency, Bengkulu Province tends to be high. A total of 46.67% of respondents were included in the category of high gadget playing duration, 36.67% were in the medium category, and 16.67% were classified as low. This shows that the use of gadgets has become a dominant activity among children in the village. The level of anxiety of parents related to the use of gadgets by their children also tends to be high. The results showed that 30% of respondents had very high levels of anxiety, 26.67% high, 25% moderate, 15% low, and 3.33% very low. The dominance of the category is very high and high, indicating significant concerns among parents regarding the impact of gadget use on their children There is a significant and positive relationship between the duration of gadget play and parental anxiety levels, with a correlation coefficient of 0.589 This suggests that the higher the duration of gadget play in children, the higher the level of anxiety experienced by parents This relationship indicates a close connection between children's gadget usage behavior and parental psychological responses.